Efficient energy Management in Industrial Sector - ONG, HAN BIN (IRC, 2019)
This paper presents the efficient in energy management in Malaysia Industrial Sector. Efficient in energy management plays a vital role in order to accommodate need of energy in the future, to conserve, preserve the resources for future generation. Besides, to protect the earth from depletion in natural resources such as fossil fuels. This process involves including monitoring, conserving and controlling energy in a building or an industry, a key to save energy in any organization. . Electricity usage in the industry are not in real- time monitoring and controlled results in wasteful of electricity consumption. This project is using 3 months data from 4 motors with same parameters ( power supply, current and voltage ) from industry and is analyzed by using energy lens software. A wide range of charts, tables and energy profiles in calendar form is created to investigate maximum, minimum or average and total energy consumption for daily, weekly and monthly. PSO algorithm in Matlab optimize the energy usage by improving load factor of each of the motor. Load factor plays a vital role in determine the efficiency of each motor as it is defined as the ratio of rated load to real load. Increasing value in load factor has proven energy has been saved and energy efficiency has been improved.